Optical fiber intelligent monitoring device for deformation of sliding type dangerous rock mass block - ZHAO SHANSHAN; WU DI; CHEN JUNHUA; LIU BAOCHEN; XU PENG; WANG XIAOBO; YANG BAI; CHENG FENG; ZHOU HAOFENG; CHEN AIJUN (2024)
The utility model discloses an intelligent optical fiber monitoring device for deformation of a sliding type dangerous rock mass block. The intelligent optical fiber monitoring device comprises a data acquisition unit, a data monitoring unit and a data processing unit, the data acquisition unit comprises an FBG sensor, an anchor rod, an optical fiber and an FBG demodulator; according to the utility model, an advanced optical fiber sensor technology and an anchoring support technology are combined, the internal structural surface of the sliding type dangerous rock mass block is monitored in real time, the measurement precision of deformation monitoring of the dangerous rock mass can be effectively improved, and meanwhile, anchoring support treatment measures are taken for the sliding type dangerous rock mass. According to the utility model, automatic real-time monitoring can be realized, and the device can be operated on site, so that on-site monitoring personnel can be helped to know the on-site deformation c